Situation evaluate on hierarchical network security based on D-S evidence theory. (1st January 2014) - Wang, Chundong; Zhang, Yu
With the development of network technology, the internet era is coming; the network security issues have become increasingly prominent. It is more important to conduct a comprehensive, accurate and quantitative evaluation for today's network security. Therefore, this paper proposed situation evaluation model for hierarchical network security based on D-S evidence theory. The model uses the information collected from multi-source sensors as source data, which was used for fusion and submitting to the upper layer based on D-S evidence theory. We combined the existing vulnerability information and threats in service layer by scanning the log files and alarm events collected from sensors with analytical hierarchy process (AHP) to decide the relative weight of each factor. After evaluating the situational values of each node on host layer, we can finally evaluate network security situational values on the whole.